2015
DOI: 10.1186/s12933-015-0197-0
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the Peroxisome Proliferator-Activated Receptor-γ (rs1801282) and its coactivator-1 (rs8192673) are associated with obesity indexes in subjects with type 2 diabetes mellitus

Abstract: ᅟThe aim of this study was to clarify whether common single nucleotide polymorphisms (SNPs) of the Peroxisome Proliferator-Activated Receptor-γ (PPAR-γ) gene (rs1801282) and the Peroxisome Proliferator-Activated Receptor-γ Coactivator-1 (PGC-1α) gene (rs8192673) are associated with obesity indexes (BMI, waist circumference) in subjects with type 2 diabetes mellitus (T2DM) in Caucasian population. The second aim was to find an association of both polymorphisms with T2DM.MethodsTwo exonic SNPs of both genes rs18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
1
17
0
1
Order By: Relevance
“…The frequency of Ala allele for PPARG polymorphism among our adolescents was similar to those found in studies with other populations, such as Polish (15.5%) [21], Chinese (10.7%) [22], and Hungarian obese children and adolescents (14.6%) [23]. Studies have reported that PPARG Pro12Ala polymorphism is associated with obesity, insulin sensitivity, and type 2 diabetes [24]. Moreover, a meta-analysis considering the presence/absence of the Ala allele (dominant effect) as the exposure and BMI as the outcome, analyzed results from 49,902 adults (Caucasian, Asian, Mexican-Hispanic, and AfricanAmerican).…”
Section: Discussionsupporting
confidence: 88%
“…The frequency of Ala allele for PPARG polymorphism among our adolescents was similar to those found in studies with other populations, such as Polish (15.5%) [21], Chinese (10.7%) [22], and Hungarian obese children and adolescents (14.6%) [23]. Studies have reported that PPARG Pro12Ala polymorphism is associated with obesity, insulin sensitivity, and type 2 diabetes [24]. Moreover, a meta-analysis considering the presence/absence of the Ala allele (dominant effect) as the exposure and BMI as the outcome, analyzed results from 49,902 adults (Caucasian, Asian, Mexican-Hispanic, and AfricanAmerican).…”
Section: Discussionsupporting
confidence: 88%
“…In diabetes mellitus, high BMI predicts the development of chronic complications (Kruzliak, Haley, Starcevic, et al, 2015;Sabaka, Kruzliak, Gaspar, et al, 2013;Valensi, Paries, Attali, & French Group for Research and Study of Diabetic Neuropathy, 2003). Few studies however described negative correlation with BMI and presence of orthostatic hypotension (Fedorowski et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Dytfeld and Horst-Sikorska29 highlighted the role of diet in metabolic disorders in patients with the PPARγ rs1801282 polymorphism and modification of the genotype by environmental factors, which can lead to diverse phenotypes. On the other hand, Kruzliak et al31 conducted analyses in a group of >1000 Caucasians with T2DM and proved that the homozygous Slovene females with wild-type alleles had lower WC in comparison with homozygous females with mutated alleles. All in all, these findings were not replicated in this study, probably due to gender and age differences.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy nonsmoking men carrying the mutant allele of rs1801282 polymorphism are at a high risk for MetS and insulin resistance 30. In a large study of the Caucasians, the rs1801282 was linked to WC in patients with T2DM 31. However, it must be remembered that other researchers found no such associations 32.…”
Section: Introductionmentioning
confidence: 99%